(untitled) (European Journal of Pure and Applied Mathematics, 2009)
In this paper we introduce a new space, the so called Q_K,ω space of analytic functions on the unit disk in terms of nondecreasing functions. The relation between integral norm of Q_K,ω space and integral norm of the weighted Bloch space B_ω is also given.